Rethinking Responsible Agency in Corporations: Perspectives from Deleuze and Guattari - Painter-Morland, Mollie (2011)
The notion of “responsibility” can be understood in a number of different ways, namely as being accountable for one’s actions, as a personal trait, or as a task or duty that results from one’s role. In this article we will challenge the assumptions that underpin each of these employments of the word “responsibility” and seek to redefine the concept as such. The main thrust of the argument is that we need to critically interrogate the idea of “identity” and deliberate decision-making that inform the use of all three of these notions of “responsibility”. By drawing on selected concepts emanating from the oeuvre of Gilles Deleuze and Félix Guattari, our understanding of agency moves away from “identity” towards “multiplicity”. In fact, it will be argued that our sense of “agency” is a side-product of our own desiring-production as it operates in and through our interactions with other human beings and organizational structures. The article therefore contends that “responsible management” requires ongoing re-articulations of moral responsiveness.
Keywords: Deleuze and Guattari; Responsibility; Agency